Toward a Monistic Theory of Science: The ‘Strong Programme’ Reconsidered. - Kemp, Stephen (Philosophy of the Social Sciences, 2003)
A study was conducted to assess the validity of the “Strong Programme” account of scientific knowledge, which assumes that the logics of interest and of instrumental adequacy are not dualistic and potentially conflicting but are one and the same. The findings, although conceding that the Strong Programme approach is flawed, differ from the more standard criticisms by suggesting that its monistic approach be refined, rather than replaced with an alternative dualistic framework.